UJI KANDUNGAN PROTEIN KASAR BIJI KACANG KOMAK (Lablab purpureus (L.) Sweet) LOKAL PULAU LOMBOK - Ervina Titi Jayanti (Bioscientist : Jurnal Ilmiah Biologi, 2017)
Abstract : Hyacinth bean (Lablab purpureus (L) Sweet) is one of highly potential legume served as a protein source, composite flour, and fodder. This legume is easily found and abundant in Lombok Island. So far,  the diversify  cation of this legume is still restricted. Improving the  quality of this crop need an assessment of their biochemical properties  particularly seed protein content. This research aimed to profiling hyacinth bean protein content based on their dry seed colour. Kjehdahl AOAC 1970 procedure used to assessed the crude protein content  while seed were obtained through exploration method to the traditional markets and farmer. During the exploration, three (3) dry seed phenotypes were found i.e dark purple, brown, and light-yellow (cream colored) seed. Crude protein content analysis showed that cream colored seed contain 13,48%, brown seed contain 11,32%, and dark purple seed of hyacinth bean contain 10,54%.